PENGGUNAAN BAHAN AJAR LEAFLET DENGAN MODEL PEMBELAJARAN TPS TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Padilah Fitriana Sari; Darlen Sikumbang; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Base in the observation on XI IPA 1 grade students of senior high school Bukit Kemuning  known that XI IPA 1 class  in even semester academic year 2011/2012 shows the average value mastery of the material of the human movement system is still lo, seen the average of student scores that 60,83 well below from the mastery learning that 65,0.  The purpose of this research was to determine the effect of the use of teaching materials leaflet with teaching models TPS towards the activity and student lerning outcomes in the subject matter of the movement system.  This research is quasi experimental with one group pretest-posttest design. A sample of this reaserch is XI IPA 1 grade students of senior high school Bukit Kemuning. The data of this study was obtained from the test (pretest and posttest) and the observation sheet (students learning activities). data analysis using a t-test with the program SPSS17.The results showed that an increased in the average between the pretest (71,73) and posttest(71,73).  The average student activity at the third metting increased by 5,88%.  Also based on the data questionnaire leaflet interest of teaching materials, all students stated instructional material leaflet in interesting (96,32%). Thus, learning to use instructional materials leaflet is effect on activity and learning outcomes of XI IPA 1 grade students of senior high school Bukit Kemuning the subject matter of the human movement system.Keywords: Leaflet, Teaching materials, TPS, Learning activities, Larning outcomes, Movement system